Combination of MLo-1508 with sunitinib for the experimental treatment of papillary renal cell carcinoma - Marques-Magalhães, Ângela; Moreira-Silva, Filipa; Graça, Inês; Dias, Paula C.; Correia, Margareta P.; Alzamora, Maria Ana; Henrique, Rui; Lopez, Marie; Arimondo, Paola B.; Miranda-Gonçalves, Vera; Jerónimo, Carmen (Frontiers in Oncology, 2025)
Renal cell carcinoma (RCC) is the 14th most incident cancer worldwide, and no curative therapeutic options are available for advanced and metastatic disease. Hence, new treatment alternatives are urgently needed to tackle disease management and drug resistance. Herein, we explored the use of MLo-1508 as an anti-tumoral agent in RCC and further assessed its combination with sunitinib for the treatment of papillary RCC. For that, different RCC cell lines were treated with both drugs, alone or in combination, and different phenotypic assays were performed. Moreover, global DNA methylation levels and specific DNMT3a activity were measured, and gene-specific CpG methylation and transcript levels were quantified after treatment. Finally, the combinatory potential of MLo-1508 and sunitinib were asses both in vitro and in vivo using the ACHN cell line. We found that MLo-1508 significantly decreased RCC cell viability while inducing apoptosis in a dose-dependent manner without cytotoxicity for non-malignant cells. Moreover, the treatment induced morphometric alterations and DNA damage in all RCC cell lines. MLo-1508 decreased DNMT1 and DNMT3A transcript levels in 786-O and ACHN cells, inhibited DNMT3A activity, and reduced the global DNA methylation content of ACHN cells. When combined with sunitinib, a reduction in ACHN cell viability, as well as cell cycle arrest at G2/M was observed. Importantly, MLo-1508 decreased the sunitinib effective anti-tumoral concentration against ACHN cell viability. In an in vivo ACHN CAM model, the combination induced cell necrosis. Thus, MLo-1508 might improve sensitivity to sunitinib treatment by decreasing the required concentration and delaying resistance acquisition.